The impact of the abolition of corporal punishment on teacher morale: 1994–2004 - Naong, Matsidiso (South African Journal of Education, 2007)
There is a direct correlation between (teacher) morale and (learner) discipline at sch ool. Since the scrapping of corporal punishment, a sense of despair seems to have taken over amongst teachers in South Africa. The findings of this study indicated that more than 65% of teachers, out of a sample population of 80 respondents from scho ols located in B loem fon tein in the Free State, claimed that discipline at schools had deteriorated, and that their passion for teaching and the joy they had once found in their work had been adversely affected since the decision had come in to effect. Amongst the many reasons for low morale, cited by the teachers, lack of dis cip line was clearly the most prevalent and common concern, and generally seemed to be attributed to the abolition of corporal punishment. I explore this concern and its impact on overall teacher morale.
Published Article